The level of technical efficiency of youngest-category gymnasts based on the phase structure of elementary floor exercises - Omorczyk, J.; Kost, M.; Dudek, D.; Bujas, P.; Nosiadek, L. (Journal of Kinesiology and Exercise Sciences, 2013)
Aim of the study. To determine the level of technical efficiency of gymnasts from the youngest sports category in elementary floor exercises. Material and methods. Study participants comprised 12 boys who trained in gymnastics in four gymnastic clubs in the Malopolskie Voivodeship. The participants were 7 and 8 years old. The study assessed their performance in floor exercises using a test developed and implemented by trainers from the aforementioned gymnastic clubs. All exercises were registered with a camera. The obtained video footage was subjected to further analysis. The performed exercises were evaluated by experts in gymnastics, who ascribed numerical values to observed errors. Each exercise was divided into movement phases, which were subjected to separate analysis by the experts. Results. The results of this study are presented in tables together with points ascribed by the experts. The technique of performing each exercise (according to all the constituent phases) was presented on the basis of elementary parameters of descriptive statistics. A synthetic indicator of technical efficiency was created by summing up the values of errors in each phase (Me = 30.00 pts). Conclusions. Study participants vary significantly in terms of technical efficiency. The greatest values of technical errors in all floor exercises performed by youngest-category gymnasts were noted in the forward roll onto arms and in the left leg cartwheel. Analysis of video footage of individual exercise phases allowed the experts to reliably spot technical errors. The analysis will enable trainers to select appropriate training methods in order to eliminate these errors.